Critical review on conventional spectroscopic α‐amylase activity detection methods: merits, demerits, and future prospects. (22nd February 2020) - Visvanathan, Rizliya; Qader, Mallique; Jayathilake, Chathuni; Jayawardana, Barana Chaminda; Liyanage, Ruvini; Sivakanesan, Ramiah
Abstract: α ‐Amylase is an endoenzyme that catalyses the hydrolysis of internal α ‐l, 4 glycosidic linkages in polysaccharides to produce maltose, maltotriose, and α ‐limit dextrins. It is widely used in the laboratorial and industrial workflow for several applications. There are several methods utilizing different techniques and substrates to assess α ‐amylase activity, among which the spectroscopic methods have found widespread applicability due to their ease of use and cost‐effectiveness. Depending upon the reaction principle, these assays are classified into four groups: reducing sugar, enzymatic, chromogenic, and amyloclastic methods. Despite the presence of numerous methods, there is no general reliable method to assess α ‐amylase activity. Each method is shown to have its own merits and demerits. Many improvements have been made to make the available methods more accurate, reliable, and easy. This communication briefly discusses the basic reaction mechanisms and critically reviews the advantages and shortcomings associated with each method. Further recommendations are made for future development. © 2020 Society of Chemical Industry